GENERATION OF CALC-ALKALINE ANDESITE OF THE TATUN VOLCANIC GROUP (TAIWAN) WITHIN AN EXTENSIONAL ENVIRONMENT BY CRYSTAL FRACTIONATION - Shellnutt J.G.; Belousov A.; Belousova M.; Wang K.L.; Zellmer G.F. (My University, 2014)
The Pliocene–Pleistocene northern Taiwan volcanic zone (NTVZ) is located within a trench-arc–back-arc basin and oblique arc–continent collision zone. Consequently the origin and tectonic setting of the andesitic rocks within the NTVZ and their relation to other circum-Pacific volcanic island-arc systems is uncertain. Rocks collected from the Tatun volcanic group (TTVG) include basaltic to andesitic rocks. The basalt is compositionally similar to within-plate continental tholeiites whereas the basaltic andesite and andesite are calc-alkaline; however, all rocks show a distinct depletion of Nb-Ta in their normalized incompatible element diagrams. The Sr-Nd isotope compositions of the TTVG rocks are very similar and have a relatively restricted range (i.e. I Sr = 0.70417–0.70488; εNd (T) = +2.2 to +3.1), suggesting that they are derived directly or indirectly from the same mantle source. The basalts are likely derived by mixing between melts from the asthenosphere and a subduction-modified subcontinental lithospheric mantle (SCLM) source, whereas the basaltic andesites may be derived by partial melting of pyroxenitic lenses within the SCLM and mixing with asthenospheric melts. MELTS modelling using a starting composition equal to the most primitive basaltic andesite, shallow-pressure (i.e. ≤1 kbar), oxidizing conditions (i.e. FMQ +1), and near water saturation will produce compositions similar to the andesites observed in this study. Petrological modelling and the Sr-Nd isotope results indicate that the volcanic rocks from TTVG, including the spatially and temporally associated Kuanyinshan volcanic rocks, are derived from the same mantle source and that the andesites are the product of fractional crystallization of a parental magma similar in composition to the basaltic andesites. Furthermore, our results indicate that, in some cases, calc-alkaline andesites may be generated by crystal fractionation of mafic magmas derived in an extensional back-arc setting rather than a subduction zone setting.
Keywords: 38.37.25 Вулканология; Татун (Тайвань); andesite; quaternary volcanism; Tatun volcanic zone; Taiwan; crystal fractionation